A Pediatric Hospital Physical Therapy and Occupational Therapy Department's Response to COVID-19: An Administrative Case Report. Issue 9 (25th June 2021) - Greenwood, Jonathan; Fragala-Pinkham, Maria; Dakhlian, Megan Geno; Brennan, Ellen; Ploski, Christine; Correia, Annette
Abstract: Objective: The purpose of this case report is to describe the challenges that COVID-19 presented for therapists in a pediatric hospital and the response to these challenges. Methods: The case report setting is a physical therapy and occupational therapy department (department) of an academic pediatric medical center that provides a range of health care services for children and youth. Challenges that COVID-19 presented to the department included (1) managing safety concerns for patients, their families, and staff; (2) continuing to provide high-quality therapy services within state-mandated restrictions; (3) triaging patients; and (4) keeping clinicians employed and working productively. Results: The department therapists responded to these challenges by (1) increasing communication huddles; (2) developing procedures for staffing and triaging of patients; (3) developing procedures for telehealth therapy services; and (4) designing a remote work program for all department employees. The number of patients and staff on site were reduced by initiating telehealth services, triaging patients, and developing a remote work plan. Communication huddles, department meetings, and supervision meetings were converted to virtual meetings. Staffing rates, patient-care productivity, and department project work were maintained. Conclusion: In response to COVID-19, the department developed new protocols and provided information about the protocols, which might be helpful for other pediatric hospitals or outpatient settings when planning for future pandemics or other issues that challenge the ability to provide usual care. Increasing the frequency of verbal and written communication on operational topics is recommended. Primary sources of information from national organizations (eg, the American Physical Therapy Association and the American Occupational Therapy Association) can assist with determining the scope of practice and code of conduct during a pandemic. Impact: COVID-19 posed challenges to operations and delivery of patient care. Although this case report is specific to COVID-19, principles applied and lessons learned from this experience can be applied to other emergency situations.